PREVALENCE OF ACETABULAR LABRAL TEARS IN ASYMPTOMATIC YOUNG ATHLETES. Issue 4 (1st February 2017) - Briggs, Karen; Philippon, Marc; Ho, Charles; McNamara, Shannen
Abstract : Background: Youth sport injuries are on the rise. These injuries at an early age may prevent young people from continuing with sports or eventually limit their ability to participate in physical activity. Objective: The purpose of this study was to determine the prevalence of acetabular labral tears in athletes 19 years of age or younger who compete in a club sport. Design: Screening Program. Setting: Youth sports. Patients (or Participants): 101 (93 males, 8 females) skiers (20) and hockey players (81) with no symptoms around the hip, no history of hip injury or surgery, and parental consent. Average age was 15 (range 11 to 19) years. Interventions (or Assessment of Risk Factors): Participants completed an initial questionnaire and had a clinical exam (hip range of motion, impingement test, hip dial test, FABER distance test). All participants had 3T MRI of dominant hip. Main Outcome Measurements: Positive exam findings and labral tear on MRI. Results: Labral tears were identified in 70 hips. Average alpha angle was 59 degrees. 89% of the participants 16 years of age or older had labral tears and 56% of the participants 16 years of younger had labral tears. Participants 16 years of older were 7 times more likely to have a labral tear [95% CI: 1.9 to 28] than participants under the age of 16. Participants who had participated in their sport 9 years or greater were 4.9 times more likely to have a labral tear [95% CI: 1.5 to 16.1] compared to participants who had participated less than 9 years. Conclusions: This study also showed a high prevalence of labral tears in the asymptomatic young athlete. Patients who were older and participated in their sport longer had increased risk of a labral tear. Limiting certain at risk movements when the young athlete is growing has potential for prevention.